Proposals for Second Five Year Plan Agricultural Sector Government of Rajasthan - Planning Commission (Planning Commission, 1955)
Agriculture contributes nearly 60% of the State income and provides employment to about 12.7 million people. The success of any plan for the economic development of Rajasthan, therefore, depends on the results achieved in making the most advantageous use of the land and labour resources engaged in agriculture. This was one of the basic principles of the First Five Year Plan and will continue to be so familiar with the Second Five Year Plan as well.
Planning Department, Government of Rajasthan